Free Exchange for Mutual Benefit: Sweatshops and Maitland’s “Classical Liberal Standard” - Carson, Thomas L. (2013)
Ian Maitland defends sweatshop labor on the grounds that “A wage or labor practice is ethically acceptable if it is freely chosen by informed workers” (he calls his view “the Classical Liberal Standard,” CLS). I present several examples of economic exchanges that are mutually beneficial and satisfy the requirements of the CLS, but, nonetheless, are morally wrong. Maitland’s arguments in defense of sweatshops are unsuccessful because they depend on the flawed “CLS.” My paper criticizes Maitland’s arguments in defense of sweatshops, but I do not claim that his conclusions are false—I do not claim to have shown that the labor practices Maitland defends are morally wrong. I argue that some of the disagreements about sweatshops between Maitland and his critics depend on disagreements about the answers controversial questions in ethical theory. In the absence of definitive answers to those questions, there are no decisive arguments for or against Maitland’s view about sweatshops.
Keywords: Ian; Maitland; Sweatshops